When I was little, like you - Malbunka, Mary. (Crows Nest, [N.S.W.] : Allen & Unwin, 2003)
As Mary Malbunka shares her stories of playing with friends, building cubby houses, climbing trees, digging for honey ants, hunting for lizards, and learning about the seasons, animals and plants, she creates a vivid picture of a truly Australian childhood in which country is life itself.
Language notes: p. [30-31].
For children.
Keywords: Malbunka, Mary, -- Childhood and youth; Aboriginal Australians -- Australia, Central -- Juvenile literature; Aboriginal Australians -- Australia, Central -- Social life and customs; Gathering - Honey; Hunting, gathering and fishing - Tracking; Stories and motifs; Indigenous knowledge - Health and medicine; Hunting, gathering and fishing; Luritja / Loritja people (C7.1) (NT SG52-04); Arrernte / Aranda language (C8) (NT SG53-02); Warlpiri people (C15) (NT SF52-04); Food - Bush tucker; Pitjantjatjara people (C6) (NT SG52-11); Pintupi people (C10) (NT SF52-11); Luritja / Loritja language (C7.1) (NT SG52-04); Pitjantjatjara language (C6) (NT SG52-11); Language; Ikuntji / Haasts Bluff (South Central NT SF52-16); Papunya (South Central NT SF52-16)